Family Financial Management Training for Farmer Housewives in Terutung Payung Hulu Village - Saddam Hasrul; Andiansyah, Farma (Business Finence Analyst Co.,, 2024)
This Family Financial Management Training activity is part of a community service program. This activity was carried out in Terutung Payung Hulu Village, Bambel District, Southeast Aceh Regency. This training activity aims to provide an understanding for residents about effective financial management plans and practices for families, helping housewives to set priorities for household needs. Assist housewives in allocating funds based on the priority of their household needs and assist housewives in allocating financial needs to the household. The program implementation method consists of socialization, providing material through lectures, then guidance and mentoring. This training was attended by 35 participants from housewives and 6 heads of households. Based on the results of the post-training evaluation, it is known that participants know that farming household financial management increases: participants are able to compile and implement financial plans well, participants can distinguish household needs based on priority needs with household consumption desires, besides that there is a change in household consumption patterns where participants can allocate household expenses ideally.